Order-disorder transition in Nano-Cu2ZnSnS4: A Raman spectroscopic study. (1st November 2019) - Kandare, S.P.; Dahiwale, S.S.; Dhole, S.D.; Rao, Mala N.; Rao, Rekha
Abstract: Quaternary compound Cu2 ZnSnS4 (CZTS) is a highly promising photo absorbing material, due to its suitability in terms of material properties, relative abundance and non-toxicity of its constituents. We report Raman spectroscopic investigation of temperature induced changes in nano-crystalline kesterite structured CZTS synthesized by microwave method. High-temperature Raman spectroscopic studies of nano-crystalline CZTS revealed relative intensity changes in the Raman spectra around the temperatures at which transition from ambient kesterite phase to disordered kesterite phase is reported by earlier neutron diffraction studies in bulk CZTS. This was also confirmed by a laser heating experiment with estimation of temperatures carried out using the Stokes/Anti-Stokes intensity ratio. The changes observed are reversible. The present results indicate a reversible transition to disordered kesterite phase at 550 K which is also achieved by laser heating.